Chiral Calcium Phosphate Catalyzed Enantioselective Synthesis of All-Carbon Quaternary Center by Friedel–Crafts Alkylation Reaction of Pyrroles and Trifluoromethylated Nitrostyrenes - Uchikura, Tatsuhiro; Yokohama, Sosuke; Murakami, Mona; Akiyama, Takahiko (Synthesis, 2022)
A chiral calcium phosphate-catalyzed enantioselective Friedel–Crafts alkylation reaction of pyrroles and α-trifluoromethyl-β-nitrostyrenes has been developed. Pyrroles bearing an all-carbon quaternary center at 2-position were obtained with high to excellent enantioselectivity. Use of 4,7-dihydroindole as a nucleophile and subsequent oxidation resulted in the formation a 2-substituted indole derivative with excellent enantioselectivity. A 3,4-dihydropyrrolo[1,2-c]pyrimidine derivative was successfully synthesized by reduction followed by benzoylation of the product without loss of enantioselectivity. Application to a 1 mmol scale reaction was successfully achieved.
Keywords: enantioselective reaction; chiral calcium phosphate; organocatalyst; trifluoromethyl group; nitrostyrene; pyrroles